IMPLEMENTATION OF FOURIER PHASE ONLY SYNTHETIS METHOD FOR 3D IMAGE PLANNING - Yuda Perwira; Wira Apriani (INFOKUM, 2019)
In carrying out the process of the Fourier Phase Only Synthetic method on two images, the observer must get the impression as if seeing the image changes its form to an intermediate form before turning into a destination image. These changes must occur regularly and consistently to achieve the goal image. This sharpening system is one of the systems that aim to process this transformation in many forms used in applications in the fields of entertainment, computer animation, scientific visualization, and education. The sharpening system on the 3-dimensional image-side aims to identify image patterns. The image quality is good if it has good contrast and can describe the structure of ridges and valleys clearly. From the implementation of the Fourier Phase Only Synthesis Analysis, using the main parameters of Ridge Orientation Image, it has been successfully obtained the results of image improvement. Improvement of this side of the image will greatly help to improve the quality of the extraction of 3-dimensional images, by determining the value of constants to get the best results.